Transition from the Exhibition to the Non-exhibition of Negative Differential Thermal Resistance in the Two-segment Frenkel-Kontorova Model - CHAN, HO-KEI (My University, 2009)
An extensive study of the one-dimensional two-segment Frenkel-Kontorova (FK) model reveals a transition from the counterintuitive existence to the ordinary nonexistence of a negative-differential-thermal-resistance (NDTR) regime, when the system size or the intersegment coupling constant increases to a critical value. A ?phase? diagram which depicts the relevant conditions for the exhibition of NDTR was obtained. In the existence of a NDTR regime, the link at the segment interface is weak and therefore the corresponding exhibition of NDTR can be explained in terms of effective phonon-band shifts. In the case where such a regime does not exist, the theory of phonon-band mismatch is not applicable due to sufficiently strong coupling between the FK segments. The findings suggest that the behavior of a thermal transistor will depend critically on the properties of the interface and the system size.
PUBLISHED
This paper presents numerical results of a comprehensive study of the conditions for the counter-intuitive occurrence of negative differential thermal resistance (NDTR) in inhomogeneous nonlinear lattices. This is important to the further development of various types of thermal devices in which NDTR is the principal operational mechanism.
Keywords: Physics